Claire Kramsch in conversation with Zhu Hua. (April 2022) - Kramsch, Claire; Hua, Zhu
Abstract : The following conversation between Zhu Hua (ZH) and Claire Kramsch (CK) was conducted on 27 October 2020 at a webinar organized by Rebecca Taylor and Rachel Tonkin from Cambridge University Press on the occasion of the impending publication of Claire's book Language as Symbolic Power and in the shadow of the imminent presidential American election. What follows are extracts from the conversation in which we have incorporated some of the questions sent in by the attendees.ZH: What motivated you to choose this topic for your book?